Neuropsychological analysis of 6-7-year-olds children in regarding their psychological readiness for schooling. (The Journal of Psychology and Sociology, 2012)
The article presents the neuropsychological analysis of 6-7-year-olds children in regarding with readiness for schooling. 6-7-yearolds children have some differences in neuropsychological status, indicating varying degrees of morphological and functional maturity of the brain. In absolute indexes, these differences are small, but statistically signiﬁ cant. 7-year-olds children in comparison with 6- year-olds children have a large maturity of prefrontal, postfrontal and basal frontal areas, and also zones of paleoencephalon brain, which are responsible for gnostic functions. 7-year-olds children in comparison with 6- year-olds children more frequently (twice) they demonstrate a high level of school maturity and therefore a high level of readiness for schooling. Correlation between developmental level of prefrontal, postfrontal and basal frontal areas of the brain and the level of school maturity was found.
Keywords: psychological readiness for schooling; neuropsychological speciﬁ cations; preschoolers.